Effect of phenolic extracts of Algerian medicinal plants on the bacterial growth and adherence of Staphylococcus aureus and Bacillus cereus pathogens responsible of food poisoning. - Imane Belkacem,; Rebai Ouafa,; Djibaoui Rachid, (International Journal of Phytomedicine, 2017)
Artemisia, one of the larger genera in the family Asteraceae, comprises from 200 to more than 500 taxa at the specific or subspecific level. Artemisia herba-alba Asso (Shih) is grown in North Africa and certain parts of Asia and Middle East. It is one of the most widely used plants in the Algerian folk medicine. The antioxidant and free radical scavenging activities of the methanolic extracted materials were tested together with their antibacterial effects against isolated bacterial strains causing food poisoning. In summary, A. herba-alba Asso represent a good phenolic and flavonoid content (161, 64 mg/g and 16,83mg/g, respectively) in comparison with T. capitatus L which represent a phenolic content of 131, 48 mg/g and 14, 96 of flavonoid content. The results shows also that the methanolic extracts of the two plants possess a strong antioxidant (DPPH, FRAP assays) and antibacterial activities, which supports their ethnopharmacological use and A. herba alba represent the highest values (IC 50: 2, 35 mg/ml and OD 1, 13 at 700nm). Our results show the interest of A. herba-alba Asso and T. capitatus L, among other medicinal plants, in search of new chemo-preventive agents against biofilm and planktonic growth of food spoilage pathogens. Further studies are envisaged to target the most interesting molecules responsible for these activities. It is concluded that organic extracts from Artemisia herba alba Asso, exert strong antioxidant activities which are related to their polyphenol contents.